Letter - Pyke, Geoffrey
036-0033-001 VOLUNTARY INDUSTRIAL AID FOR SPAIN TELEPHONE: HOLBORN 6119 32 GREAT ORMOND STREET LONDON, W.C.1 6th May 1937 ADVISORY COMMITTEE: HARRY ADAMS, Chairman (Amalgamated Union of Building Trade Workers) ALFRED BARNES, M.P. (Chairman of the Co-operative Party) A.C. BASSEBE (Hydraulic Coupling Co., Ltd.) H.G. BROTHERTON (Sheet Metal Workers Union) A.W. COSTER Electrical Trades Union) J. DUNNAGE. A.M. Inst., T. J. DAGGER (Amalgamated Society of Woodcutting Machinists) R.H. EDWARDS (National Union of Vehicle Builders) LORD FARINGDON BERT JOY (Amalgamated Society of Woodworkers) GEOFFREY PYKE, Hon. Secretary J. REEVES (Royal Arsenal Co-operative Society) JOE SCOTT, Treasurer (Amalgamated Engineering Union) J.R. SHANLEY (Amalgamated Union of Upholsterers) JACK TANNER (Amalgamated Engineering Union) Councillor D.C. WEBSTER, L.C.C. (National Union of Vehicle Builders) A.M. WALL (London Trades Council) EC/GP. 7 MAY 37 Sir Walter Citrine, K.B.E., Transport House, Smith Square, S.W.1. Dear Sir Walter, With reference to our previous correspondence, you may care to know that on Tuesday, the 4th May, the following Resolution was passed by the Surgical Branch of the Amalgamated Engineering Union:- "This Branch is prepared to support the Voluntary Industrial Aid for Spain if it* can find a practicable way of doing the work." I have some hopes that one or two firms will be willing to co-operate. All the members present undertook to give their services. Yours sincerely, Geoffrey Pyke Hon. Secretary. *(IE the Voluntary Industrial Aid) 292/946/36/33